The response to individualized treatment after a standardized treatment protocol among neck pain sufferers: a secondary analysis of a randomized controlled trial - Anders Galaasen Bakken; Andreas Eklund; Anna Oksanen; Iben Axén (Chiropractic & Manual Therapies)
Abstract Background Manual therapy and exercise are recommended for patients with neck pain. In a recent randomized controlled trial, home stretching exercises with or without manual therapy were offered to subjects with persistent or recurrent neck pain. No difference in pain or disability between the treatment groups were found after the two-week intervention period. We aimed to investigate whether these patients had a better outcome after individual tailoring of the treatment content two months after the initial structured intervention period. Methods This manuscript is a secondary analysis of a previous clinical trial where 131 patients with persistent or recurrent neck pain received treatments over two weeks (the intervention period). Pain and disability were assessed for two months following the intervention period. During this period, the treating therapists could recommend further individualized tailored treatment, including any treatment modality, regardless of the intervention group and whether the participants responded to the intervention (responders) or not (non-responders). Responders from the intervention period were defined as reporting a minimal clinical improvement on the numeric rating scale (NRS-11) at a 20-percentage points improvement (2 increments), regardless of group belonging in the original trial. All other participants were considered non-responders. We also evaluated the number of treatments, differences in disability, quality and affective component of pain, and quality of life during the individualized care period. Results For responders to a randomized trial of manual therapy and stretching exercises, a significant worsening in pain was associated with an increasing number of treatments during a two-month individualized care period. Among non-responders to the initial intervention period, improvement in neck pain disability was observed with individually tailored treatments. Conclusions For responders to a randomized trial of manual therapy and stretching, worsening pain in the individualized care period was associated with increasing numbers of individually tailored treatments. Among non-responders to the initial intervention period, improvement in neck pain disability was observed with individually tailored treatments. Trial registration: The trial was registered at ClinicalTrials.gov, registration number NCT03576846, on 23rd of June 2018.